2020
DOI: 10.1002/rcm.8605
|View full text |Cite
|
Sign up to set email alerts
|

Egg perivitelline fluid proteome of a freshwater snail: Insight into the transition from aquatic to terrestrial egg deposition

Abstract: Rationale Proteins from the egg perivitelline fluid (PVF) are assumed to play critical roles in embryonic development, but for many groups of animals their identities remain unknown. Identifying egg PVF proteins is a critical step towards understanding their functions including their roles in evolutionary transition in habitats. Methods We applied proteomic and transcriptomic analysis to investigate the PVF proteome of the eggs of Pomacea diffusa, an aerial ovipositing freshwater snail in the family Ampullarii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
(135 reference statements)
1
4
0
2
Order By: Relevance
“…Moreover, the high expression level of these genes, almost exclusively restricted to the albumen gland of P. diffusa (Ip et al, 2020), further supports this hypothesis.The perivitellin family tree agreed with those based on morphology and MT COI genetic analyses (Hayes et al, 2015), as the subunits belonging to PsSC and PdPV1 (bridgesii clade) and PcOvo and PmPV1 (canaliculata clade) grouped separately. This was further evidenced using antibodies: while bridgesii clade perivitellins are recognized by an anti-PsSC polyclonal antibody, anti-PcOvo antibodies reacted weakly.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, the high expression level of these genes, almost exclusively restricted to the albumen gland of P. diffusa (Ip et al, 2020), further supports this hypothesis.The perivitellin family tree agreed with those based on morphology and MT COI genetic analyses (Hayes et al, 2015), as the subunits belonging to PsSC and PdPV1 (bridgesii clade) and PcOvo and PmPV1 (canaliculata clade) grouped separately. This was further evidenced using antibodies: while bridgesii clade perivitellins are recognized by an anti-PsSC polyclonal antibody, anti-PcOvo antibodies reacted weakly.…”
Section: Discussionsupporting
confidence: 61%
“…During Ampullariidae transition from water to land, Pomacea eggs faced the harsh environmental conditions of the terrestrial environment, acquiring novel defences, including highly stable, non-digestible oligomeric perivitellins that became the most abundant proteins in the PVF (Dreon, Heras and Pollero, 2003;Ituarte et al, 2008Ituarte et al, , 2018Dreon, Ituarte and Heras, 2010;Pasquevich, Dreon and Heras, 2014;Pasquevich et al, 2017;Ip et al, 2019Ip et al, , 2020. In this study we isolated and characterized the main perivitellin of P. diffusa eggs, which unveiled some evolutionary trends within the genus.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to protecting the adults, it has been shown that several of these compounds are also maternally transferred to eggs where they would provide immunity to the developing embryos. For instance, recent proteomic studies revealed the presence of many proteins with defensive roles in the egg fluid-referred to as perivitelline fluid (PVF)-of several snail species including Biomphalaria glabrata, Marisa cornuarietis, Pomacea diffusa, P. canaliculata, and P. maculata (3)(4)(5)(6)(7). Among these proteins, called perivitellins, an evolutionary novelty arose in the eggs of some Pomacea species, in which two immune effectors, a perforin from the Membrane Attack Complex and Perforin (MACPF) family and a tachylectin, combined and formed a neurotoxin, the perivitellin-2 or PV2 (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, each orthologous group presents low sequence divergence, reinforcing the suggestions by Ituarte et al (Ituarte et al ., 2018), that after gene duplication the advantage of having multiple copies of this gene may enhance the perivitelline synthesis during egg production, thus preventing additional gene variations. Moreover, the high expression level of these genes, almost exclusively restricted to the albumen gland of P. diffusa (Ip et al, 2020), further supports this hypothesis.The perivitellin family tree agreed with those based on morphology and MT COI genetic analyses (Hayes et al ., 2015), as the subunits belonging to PsSC and PdPV1 ( bridgesii clade) and PcOvo and PmPV1 ( canaliculata clade) grouped separately. This was further evidenced using antibodies: while bridgesii clade perivitellins are recognized by an anti-PsSC polyclonal antibody, anti-PcOvo antibodies reacted weakly.…”
Section: Discussionmentioning
confidence: 54%
“…During Ampullariidae transition from water to land , Pomacea eggs faced the harsh environmental conditions of the terrestrial environment, acquiring novel defences, including highly stable, non-digestible oligomeric perivitellins that became the most abundant proteins in the PVF (Dreon, Heras and Pollero, 2003; Ituarte et al ., 2008, 2018; Dreon, Ituarte and Heras, 2010; Pasquevich, Dreon and Heras, 2014; Pasquevich et al ., 2017; Ip et al ., 2019, 2020). In this study we isolated and characterized the main perivitellin of P. diffusa eggs, which unveiled some evolutionary trends within the genus.…”
Section: Discussionmentioning
confidence: 99%